Improving performance of flat-plate photobioreactors by installation of novel internal mixers optimized with computational fluid dynamics. (April 2015) - Huang, Jianke; Feng, Fei; Wan, Minxi; Ying, Jiangguo; Li, Yuanguang; Qu, Xiaoxing; Pan, Ronghua; Shen, Guomin; Li, Wei
Highlights: A novel flat-plate photobioreactor with specific mixer was developed. Mixer significantly increases biomass productivity and energetic performance. Performance of novel photobioreactor optimized by CFD was further enhanced. Simulation results are validated by the experiments of microalgae cultivation. Abstract: A novel mixer was developed to improve the performance of flat-plate photobioreactors (PBRs). The effects of mixer were theoretically evaluated using computational fluid dynamics (CFD) according to radial velocity of fluid and light/dark cycles within reactors. The structure parameters, including the riser width, top clearance, clearance between the baffles and walls, and number of the chambers were further optimized. The microalgae culture test aiming at validating the simulated results was conducted indoor. The results showed the maximum biomass concentrations in the optimized and archetype reactors were 32.8% (0.89 g L −1 ) and 19.4% (0.80 g L −1 ) higher than that in the control reactor (0.67 g L −1 ). Therefore, the novel mixer can significantly increase the fluid velocity along the light attenuation and light/dark cycles, thus further increased the maximum biomass concentration. The PBRs with novel mixers are greatly applicable for high-efficiency cultivation of microalgae.